LEGAL STATUS OF ZAKAT FITRAH COLLECTION BY ZAKAT FITRAH COMMITTEES THAT DO NOT HAVE LEGITIMATE PERMITS FROM GOVERNMENT INSTITUTIONS ACCORDING TO LAW NO. 23 OF 2011 - Jailani Siregar; Hasbullah Ja’far (Bengkoelen Justice : Jurnal Ilmu Hukum, 2025)
Zakat fitrah is an obligation for every capable Muslim and must be paid during the month of Ramadan as a form of cleansing of wealth and soul. The management of zakat fitrah is usually carried out by the zakat fitrah committee in the community. However, not all zakat fitrah committees have permission or legitimacy from authorized government institutions, namely the National Zakat Amil Agency (BAZNAS) or registered zakat amil institutions. This research aims to analyze the legal status of zakat fitrah collection by a committee that does not have permission from the government based on Law no. 23 of 2011 concerning Zakat Management. This research uses a normative approach with a literature study regarding applicable legal provisions. In this study, the researcher used a statutory approach, namely an approach that analyzes and examines statutory regulations related to the legal problems currently being faced.The research results show that the collection of zakat fitrah by a committee that does not have permission or legitimacy from a government institution could potentially violate legal provisions regulated in Law no. 23 of 2011, which can cause problems regarding the legality of zakat distribution and supervision of its use. Keywords: Legal Status, Zakat Fitrah Commite, Legitimacy.